THE EFFECT OF MACROECONOMIC VARIABLES IN PREDICTING INDONESIAN SHARIA STOCK INDEX - Angga Khoerul Umam; Ririn Tri Ratnasari; Sri Herianingrum (Universitas Airlangga, 2019)
ABSTRACTThis study examines the impact of macroeconomic variables, namely the exchange rate, interest rates, industrial production index, SBIS and inflation on the Indonesian Islamic stock index. This study uses monthly data from May 2011 to December 2018. This research is a quantitative study that applies the Johansen Cointegration Test and Vector Error Correction Model to see the long-term impact and shock response on certain variables. The findings indicate the existence of short-term and long-term causality between macroeconomic variables and the Indonesian Islamic stock index. Especially in the long run, industrial production index and inflation have a significant effect on ISSI, while the exchange rate, interest rates and SBIS have no significant effect on ISSI. IRF results show that the response of each variable and stable at different times. The ISSI response experienced a positive shock that occurred in the industrial production index and inflation. On the other hand, the exchange rate, the Bungan rate and SBIS were responded negatively by ISSI.